Total cross sections for electron scattering from noble-gas atoms in near- and below-thermal energy collisions. (November 2015) - Kitajima, M; Shigemura, K; Hosaka, K; Odagiri, T; Hoshino, M; Tanaka, H
Abstract: Absolute total cross sections for electron scattering from He, Ne, Ar, Kr and Xe at very low electron energies are presented. The cross sections were obtained using the threshold- photoelectron source, which employs a combination of the penetrating field technique together with the threshold photoionization of atoms by synchrotron radiation. Obtained total cross sections for electron scattering from these noble gas atoms generally agree well with those obtained in the previous experiments above 100 meV, where several experimental works have been reported. Comparison of the measured cross section for He with that of theoretical ones shows very good agreement at very low energies even below 10 meV, which confirms the validity of theoretical cross sections of He which have been regarded as the 'standard' cross sections. Scattering lengths for the e - - noble gas scatterings determined from the our cross sections using the modified effective range theory (MERT) showed that scattering lengths for He and Ne agree well with the values obtained in the previous experimental and theoretical studies. On the other hand, in case of heavier noble gas atoms, significant discrepancies were found between the scattering lengths derived from MERT analysis to our total cross sections and those reported in previous studies.